Impact of Work Distributive Justice on Patient’s Satisfaction: Mediating Roles of Nurses’ Work Performance - Alshammari, Waleed Mansi; Ali, Dhakir Abbas (Journal of Social and Development Sciences, 2024)
In any organization justice in work distribution is crucial. This justice in the work distribution increases the confidence of the workers and provides equality among other worker. Therefore, the objective of this study is to investigate the relationship between work distribution justice and patient satisfaction in the context of the Hail health cluster. Further, to examine the role of work performance as a mediator. The study employed a quantitative research design, utilizing a sample of 327 nurses working within the Hail Health Cluster. Data was collected through structured questionnaires from May to July 2024, after the data analysis SEM-PLS was used to extract the results. The findings reveal a significant positive relationship between distributive justice and patient satisfaction, with nurses’ performance acting as a vital mediator. Results indicate that equitable distribution of workloads, recognition, and resources among nursing staff not only enhances their performance but also leads to improved patient satisfaction levels. The mediating effect of nurses’ work performance underscores the importance of distributive justice as a fundamental factor in healthcare management that enhances patient care outcomes. This research highlights the need for healthcare administrators to implement fair and transparent policies regarding workload distribution to foster an environment that supports high-quality nursing performance, ultimately benefiting patient care and satisfaction.